Les réseaux de la qualité de l’air : des associations stratèges actrices de l’action publique - Franck Boutaric (Développement Durable et Territoires)
This article highlights the capacity of air pollution control agencies to unite together to build coalitions advocating the formation and implementation of public policies aimed at reducing atmospheric pollution. Amongst the various settings for exchange and confrontation (within the industry, associations, politics, advisory boards), networks of air pollution control agencies have asserted their skills and expertise in the promotion of their missions and objectives. Their ability to participate in the development of tools for public action, such as information and alerte procedures and the air quality index (atmo index), attest to the role they play in managing public policies in the years both preceding and following the passing of the energy conservation law on the rational use of energy. In the end, the study of tools of public action is one of the significant approaches for understanding some of the mechanisms of change in a public policy. Among those mechanisms appear the networks of air pollution agencies.